Are we ready to integrate 3D culture systems in acute myeloid leukemia and bone marrow microenvironment research? - Sharipol, Azmeer; Frisch, Benjamin J. (Frontiers in Hematology, 2024)
Acute myeloid leukemia (AML) is the most aggressive adult leukemia and results in a dismal 5-year survival rate of less than 30%. While research has primarily focused on identifying intrinsic mutations driving leukemogenesis, the role of the bone marrow microenvironment (BMME) in disease progression remains poorly understood. For this purpose, conventional 2D cultures inadequately replicate the complex BMME interactions crucial for the maintenance of normal hematopoiesis and leukemia pathogenesis. In recent years, 3D cultures or microphysiological systems (MPS), have emerged as promising tools for in vitro modeling of the human BMME. These approaches provide a promise for a more physiologically relevant platform for investigating the mechanistic underpinnings of AML interactions with BMME components, as well as exploring chemoresistance mechanisms and facilitating drug discovery efforts. This review discusses the considerations in biomaterials, biophysical, and biochemical factors to develop the BMME in vitro for AML studies, the state-of-the-art 3D models of the BMME, and the challenges and prospects of adopting MPS for AML research.